Nesting in anticipation: Spatial ecology of giant honey bees (Apis dorsata) in relation to crop succession mapped by remote sensing - Gerald Kastberger; Wolfgang Sulzer (PLoS ONE, 2026)
Seasonal migration and nesting of the giant honeybee Apis dorsata (Fabricius, 1793) are widely associated with mass-flowering crops, yet how colony settlement relates to surrounding landscape structure remains poorly understood. We analysed land-use patterns within the effective foraging range of A. dorsata colonies in the central Chitwan plain, Nepal, using satellite-derived land-use maps from three seasonal snapshots spanning one agricultural cycle: December 1999, February 2000, and April 2000. For each season, land-use composition was quantified radially around nesting sites and compared with spatially constrained random reference landscapes, allowing background seasonal turnover to be separated from nest-specific spatial contrasts. To evaluate both the magnitude and spatial consistency of these contrasts across colonies, we developed a signal–precision framework that integrates contrast strength with repeatability across 55 nesting sites, comprising approximately 300 nests, and 55 matched random locations. Across seasons, the strongest nest-associated signals corresponded to two nectar- and pollen-relevant crops: mustard in December 1999 and buckwheat in February 2000. These signals peaked within 1–3 km of nests, consistent with the effective foraging range of A. dorsata , whereas the distinction between nest-centred and random landscapes became less pronounced at larger distances. Although mustard and buckwheat covered smaller proportions of the landscape than dominant cereals, such as wheat and rice, or other land-use classes, including grassland and fallow land, they consistently emerged as the most spatially precise nest-associated components, highlighting their diagnostic relevance for nesting environments. By separating nest-specific signals from seasonal land-use change and quantifying both their strength and spatial consistency, our colony-centred, null-model-based framework reveals how large-scale agricultural structure becomes reflected in colony settlement patterns. Through interannual return to traditional nesting sites, colony fidelity interacting with structured agricultural dynamics generates distinct nest-centred signals for forage-relevant crops, producing a pattern consistent with apparent anticipation of future resource availability. Although based on data from 1999–2000, this study provides a historical baseline of colony–landscape relationships, with ongoing work aimed at evaluating their persistence under current conditions.